Magnetic nanodiscs that destroy glioblastoma cells in a targeted way in an alternating nonheating magnetic field - Fedotovskaya, Victoriya D.; Zamay, Sergey S.; Zotova, M. V.; Masyugin, Albert N.; Zelenov, Fyodor V.; Luzan, Natalia A.; Zamay, Tatiana N.; Koshmanova, Anastasia A.; Kirichenko, Daria A.; Nikolaeva, Elena D.; Kolovskaya, Olga S.; Shchugoreva, Irina A.; et al. (Nanobiotechnology reports)
The need to develop a surgical instrument that can most effectively and minimally invasively remove a malignant tumor, and distinguish and destroy only tumor cells without damaging the normal cells of healthy tissue surrounding the tumor is being considered. To achieve this goal, it is proposed to use nanodiscs with special magnetic, electronic and optical properties. Nanodiscs modified with recognition ligands (aptamers) are able to bind to tumor cells and destroy them under the influence of a weak, nonheating alternating magnetic field. This allows for effective tumor destruction while minimizing the impact on surrounding healthy tissue.